Degradation Mechanism of Phenethylamine‐Based Interlayers in Perovskite Solar Cells and Breakthrough. Issue 7 (4th April 2023) - Lee, Seri; Kim, Gyu Min; Miyasaka, Tsutomu; Oh, Se Young
Abstract : Perovskite Solar Cells In article number 2201002, Gyu Min Kim, Se Young Oh, and co‐workers presented the incorporation of an insulating layer (poly(methyl methacrylate), PMMA) at the perovskite/phenethylamine halides (PEAX) interface to form a dual PMMA/PEAX interlayer. They found that thermal treatment on this dual interlayer further enhances the dipole moment from PEAX, thereby improving open circuit voltage and stability of perovskite solar cells simultaneously.